1997
DOI: 10.1128/jb.179.22.6994-7003.1997
|View full text |Cite
|
Sign up to set email alerts
|

General secretion pathway (eps) genes required for toxin secretion and outer membrane biogenesis in Vibrio cholerae

Abstract: The general secretion pathway (GSP) of Vibrio cholerae is required for secretion of proteins including chitinase, enterotoxin, and protease through the outer membrane. In this study, we report the cloning and sequencing of a DNA fragment from V. cholerae, containing 12 open reading frames, epsC to -N, which are similar to GSP genes of Aeromonas, Erwinia, Klebsiella, Pseudomonas, and Xanthomonas spp. In addition to the two previously described genes, epsE and epsM (M. Sandkvist, V. Morales, and M. Bagdasarian, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
204
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(216 citation statements)
references
References 76 publications
10
204
0
Order By: Relevance
“…When GFP-EpsL and native EpsM were coexpressed from two different plasmids in the same E. coli cells, the level of GFP-EpsL fluorescence was increased (Fig. 1F), thus confirming the previous finding that showed that EpsM stabilizes EpsL and prevents its degradation (34). Furthermore, in the presence of EpsM, GFP-EpsL was detected at the cell poles in E. coli (Fig.…”
Section: Polar Distribution Of Eps Componentssupporting
confidence: 78%
See 2 more Smart Citations
“…When GFP-EpsL and native EpsM were coexpressed from two different plasmids in the same E. coli cells, the level of GFP-EpsL fluorescence was increased (Fig. 1F), thus confirming the previous finding that showed that EpsM stabilizes EpsL and prevents its degradation (34). Furthermore, in the presence of EpsM, GFP-EpsL was detected at the cell poles in E. coli (Fig.…”
Section: Polar Distribution Of Eps Componentssupporting
confidence: 78%
“…1A). GFP was also fused to the N terminus of the cytoplasmic membrane protein EpsM, which has previously been shown to interact with EpsL (34), to determine whether the polar location is common to other Eps proteins. Like GFP-EpsL, this fusion protein was also active and could restore extracellular secretion in a V. cholerae epsM mutant (not shown).…”
Section: Polar Distribution Of Eps Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Often, the gene that encodes the type 4 prepilin peptidase is found at the end of the secretory locus. However, no prepilin peptidase has been identified within the eps gene cluster (Sandkvist et al, 1997). V. cholerae O1 is classified into two biotypes, classical and El Tor, based on several biochemical and phenotypic properties. One of these properties is the ability to mediate mannose-sensitive haemagglutination, an activity that is generally associated with the El Tor biotype but not with the classical biotype (Finkelstein and Mukerjee, 1963).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, a cluster of 10 genes (CTC1596-CTC1605) could be identified with similarities to subunits of type II secretion and type IV pilus biogenesis systems. Two ORFs (CTC1604, CTC1603) show strong similarities to the subunits EpsE and F of the type II secretion system in V. cholerae, which is responsible for the export of the cholera toxin (44). Three additional ORFs within the C. tetani cluster show some homology to EpsG, -H, and -I.…”
mentioning
confidence: 99%